Comparative immunological characterization of type-specific and conserved B-cell epitopes of pinniped, felid and canid herpesviruses. - Lebich, M.; Harder, T.C. (Timm); Frey, H.R.; Visser, I.K.G. (Ilona); Osterhaus, A.D.M.E. (Albert); Liess, B. (Archives of Virology, 1994)
Murine monoclonal antibodies (MAbs) were generated against phocid herpesviruses (PhHV 2557/Han88 and 7848/Han90) isolated from European harbour seals (Phoca vitulina), and against strains of both felid (FHV strain FVR 605) and canid herpesviruses (CHV isolate 5105/Han89). MAbs were characterized with respect to certain biological properties and used to outline antigenicity profiles of isolates of PhHV (n = 8), FHV (n = 7) and CHV (n = 3) in enzyme immunoassays employing fixed infected ce